PENGEMBANGAN BAHAN AJAR BUKU SAKU MATEMATIKA BERBASIS PENDIDIKAN KARAKTER MATERI TRIGONOMETRI - Budi Cahyono; Dian Tsani; Aulia Rahma (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2018)
This development research is motivated because students need practical teaching materials when studied in class or outside the classroom. Religious characteristics and politeness of low students demand to reduce character values in teaching materials, so as to improve learning achievement and improve the character's value of participants student. This research is a type of R D research with the procedure for developing pocket books using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subject of this study was the students of MA Sunan Katong class X with data analysis techniques using descriptive qualitative and quantitative. Based on the results of the study it can be concluded that mathematical pocket books based on character education on trigonometry material are feasible to use. Test the validity by evaluating the validator included in the valid category but needs to be slightly revised with an average percentage of 70.80%. The response of students to pocket books is included in the excellent category with a percentage of 86.60%. The results of the t-test get the result t_count = 2,248 t_table = 1,668 then H_1 is accepted. This means that the class average using mathematical pocket books based on character education is better than those that do not use pocket books. The n-gain score is 0.34. This shows that learning uses a pocket book of trigonometry based on character education to effectively improve the character education of students in the medium category.